Factors associated with early childhood caries incidence among high caries‐risk children. Issue 4 (16th March 2015) - Ghazal, Tariq; Levy, Steven M.; Childers, Noel K.; Broffitt, Barbara; Cutter, Gary R.; Wiener, Howard W.; Kempf, Mirjam C.; Warren, John; Cavanaugh, Joseph E.
Abstract Objectives To assess the relationships between different behavioral factors and Early Childhood Caries (ECC) in African‐American pre‐school children. Methods Ninety‐six African‐American children aged 3–22 months old at baseline were recruited from a high caries risk, non‐fluoridated African‐American community in Uniontown, Alabama. The children had dental examinations annually following World Health Organization (WHO) criteria at mean ages 1.1, 2.0, 3.1 and 4.0 years. All children received fluoride varnish application at each study visit. Parents provided oral hygiene and dietary information semiannually by completing questionnaires. Area‐under‐the‐curve (AUC) with the trapezoidal rule was used to summarize longitudinal exposure data. Bivariate and multivariable relationships between ECC incidence and behavioral risk factors were assessed using logistic regression and negative binomial modeling for dichotomous and count dependent variables, respectively, with the independent variables defined at age 1, age 3 and as the AUC. Results Greater frequency of toothbrushing and greater AUC composite of daily frequency of consumption of 100% juices were associated with lower incidence of dental caries (P‐values = 0.01 and 0.049, ORs = 0.34 and 0.37, respectively). Greater AUC of daily frequency of consumption of sweetened foods and history of a previous visit to a dentist by age 3 were associated with greater incidence of ECC (ORs = 9.22 and 4.57, P‐values = 0.002 and 0.03, respectively). Conclusion For these children living in a non‐fluoridated community, more frequent consumption of sweetened food, less frequent consumption of 100% juice, less frequent toothbrushing, and reporting a previous visit to a dentist were significantly associated with greater ECC incidence.